Victimization Disparities Between Heterosexual and Sexual Minority Youth From Ages 9 to 15. Issue 1 (25th June 2018) - Martin‐Storey, Alexa; Fish, Jessica
Abstract : Mental health disparities between heterosexual and sexual minority youth are partly explained by the higher rates of victimization experienced by sexual minority youth. The onset and progression of these victimization disparities, however, are poorly understood. Using multirater longitudinal data, trajectories of victimization starting at age 9 were compared among youth who did and did not report same‐sex attraction at age 15 ( N = 310). Self and teacher, but not primary caregivers, reported victimization was significantly higher among sexual minority youth starting at age 9, but did not vary across time. The findings underscore the importance of understanding homophobic experiences of sexual minority youth during late childhood and early adolescence in order to inform prevention programs.